THE METHODICAL COMPETENCIES’ PROPAEDEUTIC OF THE FUTURE PRIMARY SCHOOL TEACHERS AT THE NATURAL SCIENCE LECTURES IN HIGH SCHOOL - Solovyeva, Tatiana; Karpovich, Olesia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article characterizes and experimentally substantiates the criteria, indicators and levels of methodical competence of future teachers; illustrated by didactic means propaedeutic training of students for the instructional activities in primary school. The influence of metaprofessional (universal) instrumental competences formed by future teachers at Nature Science lectures on the unconscious, on the intuitive level, through the "insight", their acquisition of the methodological experience is proved.